S32006, a novel 5-HT2C receptor antagonist displaying broad-based antidepressant and anxiolytic properties in rodent models. - Dekeyne, A; Mannoury la Cour, C; Gobert, A; Brocco, M; Lejeune, F; Serres, F; Sharp, T; Daszuta, A; Soumier, A; Papp, M; Rivet, J; Flik, G; et al. (2008)
RATIONALE: Serotonin (5-HT)(2C) receptors are implicated in the control of mood, and their blockade is of potential interest for the management of anxiodepressive states. OBJECTIVES: Herein, we characterized the in vitro and in vivo pharmacological profile of the novel benzourea derivative, S32006. MATERIALS AND METHODS: Standard cellular, electrophysiological, neurochemical, and behavioral procedures were used. RESULTS: S32006 displayed high affinity for human (h)5-HT(2C) and h5-HT(2B) receptors (pK (i)s, 8.4 and 8.0, respectively). By contrast, it had negligible (100-fold lower) affinity for h5-HT(2A) receptors and all other sites examined. In measures of Gq-protein coupling/phospholipase C activation, S32006 displayed potent antagonist properties at h5-HT(2C) receptors (pK (B) values, 8.8/8.2) and h5-HT(2B) receptors (7.8/7.7). In vivo, S32006 dose-dependently (2.5-40.0 mg/kg, i.p. and p.o.) abolished the induction of penile erections and a discriminative stimulus by the 5-HT(2C) receptor agonist, Ro60,0175, in rats. It elevated dialysis levels of noradrenaline and dopamine in the frontal cortex of freely moving rats, and accelerated the firing rate of ventrotegmental dopaminergic and locus ceruleus adrenergic neurons. At similar doses, S32006 decreased immobility in a forced-swim test in rats, reduced the motor depression elicited by 5-HT(2C) and alpha(2)-adrenoceptor agonists, and inhibited both aggressive and marble-burying behavior in mice. Supporting antidepressant properties, chronic (2-5 weeks) administration of S32006 suppressed "anhedonia" in a chronic mild stress procedure and increased both expression of BDNF and cell proliferation in rat dentate gyrus. Finally, S32006 (0.63-40 mg/kg, i.p. and p.o) displayed anxiolytic properties in Vogel conflict and social interaction tests in rats. CONCLUSION: S32006 is a potent 5-HT(2C) receptor antagonist, and possesses antidepressant and anxiolytic properties in diverse rodent models.